The effect of Corporate Social Responsibility (CSR), institutional ownership, and audit quality on tax avoidance: A study of basic material companies listed on the Indonesia Stock Exchange for the period 2020-2024 - Karina Windara; Linda Santioso (Educoretax, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR), institutional ownership, and audit quality on tax avoidance in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Tax avoidance remains a persistent issue in the basic materials sector because of its large operational activities, asset values, and transactions, which open opportunities for aggressive tax planning. This research employs a quantitative approach with a causal design using secondary data obtained from annual reports and audited financial statements. The sampling technique used was purposive sampling, resulting in 24 companies with a total of 120 observations after outlier removal. Data were analyzed using panel data regression with EViews 14, where the Random Effect Model (REM) was selected through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results show that CSR has a positive but insignificant effect on tax avoidance, institutional ownership has a negative and significant effect on tax avoidance, and audit quality has a negative but insignificant effect on tax avoidance. Simultaneously, the three independent variables significantly affect tax avoidance, with an Adjusted R-squared value of 5.1%. These findings imply that institutional ownership functions as an effective monitoring mechanism that discourages aggressive tax planning, while CSR disclosure and audit quality have not become the main determinants of corporate tax avoidance behavior in the basic materials sector.